Does Allocation of Attention Influence Relative Velocity and Strength of Illusory Line Motion? - Hubbard, Timothy L.; Ruppel, Susan E. (Frontiers in Psychology, 2018)
In illusory line motion, presentation of a cue is followed by presentation of a nearby stationary line, and the line is perceived to “unfold,” “expand,” or “extend” away from the cue. Effects of the allocation of attention regarding where the cue or the line would be presented were measured in three experiments, and ratings of relative velocity and relative strength of illusory motion were collected. Findings included (a) relative velocity and relative strength decreased with increases in SOA from 50 to 450 milliseconds, (b) relative velocity and relative strength were not influenced by whether illusory motion moved from one end of the line to the other or from both ends toward the middle of the line, (c) increased uncertainty regarding where the line would appear did not influence relative velocity or relative strength, and (d) valid pre-cues regarding the location of a cue resulted in faster relative velocity than did invalid pre-cues, but pre-cue validity did not influence relative strength. Implications of these findings for the relationship of such illusory motion and attention (e.g., divided attention, shifts in attended location) are considered.